Entrepreneurial orientation, market orientation, network ties, and performance: Study of entrepreneurial firms in a developing economy - Boso, Nathaniel; Story, Vicky M.; Cadogan, John W. (Journal of Business Venturing, 2013)
Entrepreneurial orientation (EO), market orientation (MO) and network ties are typically modeled as separate antecedents of performance. However, the boundary conditions for such models are under-explored, as is their applicability to developing economy settings. Accordingly, drawing on institutional and social capital theories, the current paper argues that the performance benefits of EO and MO are complementary, and vary across different levels of social and business network ties. Using primary data gathered from entrepreneurial firms operating in Ghana, the study findings indicate that aligning high levels of EO and MO improves business performance, and particularly so when social and business network ties are well developed, since under these latter conditions, the performance benefits of aligning EO and MO are greatest.